A GENERALISATION OF THE DIOPHANTINE EQUATION x^2+8∙7^b=y^2r - Sapar, Siti Hasana; Yow, Kai Siong (Malaysian Journal of Science, 2021)
We investigate the integral solutions to the Diophantine equation where . We first generalise the forms of and that satisfy the equation. We then show the general forms of non-negative integral solutions to the equation under several conditions. We also investigate some special cases in which the integral solutions exist.